2010
DOI: 10.1002/ejoc.201001278
|View full text |Cite
|
Sign up to set email alerts
|

N‐Benzyl‐2,3‐trans‐Carbamate‐Bearing Glycosyl Donors for 1,2‐cis‐Selective Glycosylation Reactions

Abstract: Glycosyl donors for the preparation of 1,2‐cis glycosides of amino sugars have been developed. The 2,3‐trans‐cyclic‐carbamate‐carrying glycosyl donors were readily prepared from the corresponding known trichloroethyl carbamate protected amino sugars under standard hydroxy group benzylation conditions. The donors exhibit high 1,2‐cis stereoselectivity towards secondary hydroxy group substrates. In the case of primary hydroxy acceptors, high stereoselectivities were achieved with the aid of the dioxane effect. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 121 publications
1
20
0
Order By: Relevance
“…38 Concerning the influence of cyclic protecting groups on the anomeric equilibrium, we noted that a 2N,3O-oxazolidinone in the glucosamine series both facilitates the interconversion of β- to α-anomers and strongly favors the α-anomer. 23 Similar observations were made by the Oscarson, Ye, and Ito groups, 25,26,40,28,29,4143 all of which concluded that the equilibration occurs via an endocyclic cleavage mechanism.…”
Section: Introductionsupporting
confidence: 70%
“…38 Concerning the influence of cyclic protecting groups on the anomeric equilibrium, we noted that a 2N,3O-oxazolidinone in the glucosamine series both facilitates the interconversion of β- to α-anomers and strongly favors the α-anomer. 23 Similar observations were made by the Oscarson, Ye, and Ito groups, 25,26,40,28,29,4143 all of which concluded that the equilibration occurs via an endocyclic cleavage mechanism.…”
Section: Introductionsupporting
confidence: 70%
“…125,129 Ito and coworkers showed the N -benzyloxazolidinone protected glucosamine donor 78 (Fig 8) to be unselective at low temperatures and α-selective at room temperature and, like Oscarson, came to the conclusion that this was the result of an equilibration process involving endocyclic cleavage. 130 …”
Section: Derivatives Of N-acetylglucosaminementioning
confidence: 99%
“…19 In particular, in recent years, cyclic protecting groups 10 have proven to be especially useful in controlling the stereochemistry of what were previously considered to be difficult glycosylations. Prominent examples include the 4- O ,5- N -oxazolidinones in the sialic acid series, 1115 the 3,5- O -(di- tert butyl) silylene acetals and related groups in the arabinofuranoside series, 1618 the 2 N ,3 O -oxazolidinones in the 2-amino-2-deoxyglucopyranose series, 1921 and the 4,6- O -benzylidene acetals in both the gluco- 2223 and mannopyranoside series. 2425 In most cases mechanistic understanding lags someway behind application of these mostly serendipitous discoveries owing to the complex nature of glycosylation reactions, but significant progress has been made on the origins of the 4,6- O -benzylidene effect in gluco- and mannopyranosylation.…”
Section: Introductionmentioning
confidence: 99%